Profiling of lipid mediators in atherosclerotic carotid plaques from type 2 diabetic and non-diabetic patients. (September 2022) - Ménégaut, Louise; Laubriet, Aline; Crespy, Valentin; Nguyen, Maxime; Petit, Jean-Michel; Tarris, Georges; Pilot, Thomas; Varin, Alexis; Choubley, Hélène; Bergas, Victoria; de Barros, Jean-Paul Pais; Thomas, Charles; et al.
Highlights: Type 2 diabetics patients and non diabetic patients display a similar profile of lipid mediators in atherosclerotic carotid plaques. Leukotriene B4 is detected at significant levels in carotid atheroma plaques and is highly correlated with 5-Hydroxyeicosatetraenoic acid concentrations. Docosahexaenoic acid enrichment in carotid plaques correlates negatively with 5-Hydroxyeicosatetraenoic acid concentrations. Abstract: Background and aims: Diabetes is associated with an accelerated development of atherosclerosis. Specific mechanisms related to diabetes and hyperglycemia may play a role in this process. In particular, alterations of arachidonic acid (AA) metabolism have been reported. Our main goal was to investigate for differences in the concentration of LTB4 and RvD1 as well as selected cyclooxygenase-derived mediators in carotid plaques from diabetic and non-diabetic patients. We also aimed to analyze the relationship between omega 6 and omega 3 Poly-Unsaturated Fatty acids (PUFAs) content in the plaques and the concentrations of these lipid mediators. Methods: 29 type 2 diabetic patients and 30 control patients admitted for surgical treatment of carotid stenosis were enrolled in the present study. Carotid plaques were harvested for in-depth lipidomic profiling. Results: No differences for LTB4 or other lipid mediators were observed between diabetic and non-diabetic patients. RvD1 levels were below the threshold of quantification in most of the samples. A significant correlation was found between LTB4 and 5( S )-HETE levels. Omega 3 enrichment was not significantly different between control and diabetic plaques. There was a negative correlation between DHA/AA ratio and the level of 5( S )-HETE while there was a positive association with TXB2 and PGD2 concentrations. Conclusion-perspectives: Our results does not support the hypothesis of a specific involvement of LTB4 or COX-derived mediators in diabetic atherosclerosis. The relationship between DHA enrichment and the concentrations of specific inflammatory mediators within the plaque is of interest and will need to be confirmed in larger studies.